Involvement of protein kinase C in 5-HT-stimulated ciliary activity in Helisoma trivolvis embryos - Christopher, Kimberley J (Blackwell Science Inc, 1999)
1. During development, embryos of the pulmonate gastropod, Helisoma trivolvis, undergo a rotation behaviour due to the co-ordinated beating of three bands of ciliated epithelial cells. This behaviour is in part mediated by the neurotransmitter serotonin (5-HT) released from a pair of identified embryonic neurons. Using time-lapse videomicroscopy to measure ciliary beat frequency (CBF) in response to pharmacological manipulations, we determined whether protein kinase C (PKC) is involved in mediating 5-HT-stimulated ciliary beating. 2. Diacylglycerol (DAG) analogues sn-1,2-dioctanoyl glycerol (DiC(8); 100 μM) and 1-oleoyl-2-acetyl-sn-glycerol (OAG; 100 μM), partially mimicked the 5-HT-induced increase in CBF. In contrast, application of OAG in the absence of extracellular Ca(2+) did not result in an increase in CBF. 3. 5-HT-stimulated CBF was effectively blocked by PKC inhibitors bisindolylmaleimide (10 and 100 nM) and calphostin C (10 nM). In addition, bisindolylmaleimide (100 nM) inhibited DiC(8)-induced increases in CBF. At a higher concentration (200 nM), bisindolylmaleimide did not significantly reduce 5-HT-stimulated cilio-excitation. 4. Two different phorbol esters, phorbol 12-myristate 13-acetate (TPA; 0.1, 10 or 1000 nM) and phorbol 12β, 13α-dibenzoate (PDBn; 10 μM) did not alter basal CBF. TPA (1 μM) did not alter 5-HT-stimulated CBF. Likewise, the synthetic form of phosphatidylserine, N-(6-phenylhexyl)-5-chloro-1-naphthalenesulphonamide (SC-9; 10 μM), did not increase CBF, whereas a strong increase in CBF was observed upon exposure to 5-HT. 5. The results suggest that a DAG-dependent, phorbol ester-insensitive isoform of PKC mediates 5-HT-stimulated CBF in ciliated epithelial cells from embryos of Helisoma trivolvis.